Estimación de la radiación solar global incidente en superficies inclinadas (ING) - Wright, Jaime (1992)
Monthly averages of daily global radiation incident upon a tilted southfacing surface were computed from the available values of global, direct or diffuse solar radiation incident upon a horizontal surface for Limón, Fabio Baudrit, Palmar Sur and Santa Rosa. Also there were computed monthly averages hourly values of global radiation for tilt angles of 10 and 30 degrees, with experimental data in Heredia over the period from Abril to June of 1991.In order to obtain the maximum output from a solar energy system, it is found by using different models, that the collector optimum tilt angle has to be in the range 5-30 degrees, for September, October, November, December, January and February, and 0 degrees for the other months of the year; with higher angles in January and December. Also it is found, by using experimental data in Heredia, that 0 degrees is the optimum hourly tilt angle for April, May and June.The curves in this paper will be useful for large scale installations of solar collectors or photovoltaic panels in terrain with variable slopes in the geographic regions of the Central Valley (represented by Fabio Baudrit), North Pacific (represented by Santa Rosa), South Pacific (represented by Palmar Sur) and the Atlantic (represented by Limón).